A cluster randomised feasibility trial evaluating six-month nutritional interventions in the treatment of malnutrition in care home-dwelling adults: recruitment, data collection and protocol. Issue 1 (December 2015) - Stow, Ruth; Rushton, Alison; Ives, Natalie; Smith, Christina; Rick, Caroline
Abstract Background Protein energy malnutrition predisposes individuals to disease, delays recovery from illness and reduces quality of life. Care home residents are especially vulnerable, with an estimated 30%–42% at risk. There is no internationally agreed protocol for the nutritional treatment of malnutrition in the care home setting. Widely used techniques include food-based intervention and/or the use of prescribed oral nutritional supplements, but a trial comparing the efficacy of interventions is necessary. In order to define outcomes and optimise the design for an adequately powered, low risk of bias cluster randomised controlled trial, a feasibility trial with 6-month intervention is being run, to assess protocol procedures, recruitment and retention rates, consent processes and resident and staff acceptability. Methods Trial recruitment began in September 2013 and concluded in December 2013. Six privately run care homes in Solihull, England, were selected to establish feasibility within different care home types. Residents with or at risk of malnutrition with no existing dietetic intervention in place were considered for receipt of the allocated intervention. Randomisation took place at the care home level, using a computer-generated random number list to allocate each home to either a dietetic intervention arm (food-based or prescribed supplements) or the standard care arm, continued for 6 months. Dietetic intervention aimed to increase daily calorie intake by 600 kcal and protein by 20–25 g. Results The primary outcomes will be trial feasibility and acceptability of trial design and allocated interventions. A range of outcome assessments and data collection tools will be evaluated for feasibility, including change in nutrient intake, anthropometric parameters and patient-centric measures, such as quality of life and self-perceived appetite. Conclusions The complexities inherent in care home research has resulted in the under representation of this population in research trials. The results of this feasibility trial will be used to inform the development and design of a future cluster randomised controlled trial to compare food-based intervention with prescribed oral nutritional supplements (ONS) in the treatment of malnutrition within the care home population. Trial registration Current Controlled TrialsISRCTN38047922